Clinical Overview of REM Sleep Behavior Disorder - Porter, Verna R.; Avidan, Alon Y. (Seminars in Neurology, 2017)
Rapid eye movement (REM) sleep behavior disorder (RBD) is a parasomnia characterized by loss of muscle atonia during REM sleep that allows motor responses to dream content. Patients display patterns of unusual, complex, and even violent motor activities. There is a high risk for harm to the patients or their bedpartners. REM sleep behavior disorder is more likely to occur in synucleinopathies such as Parkinson's disease, Lewy body dementia, and multiple system atrophy and may precede clinical manifestations by decades. In secondary RBD, brainstem centers involved in muscle atonia during REM are disrupted. These conditions include multiple sclerosis, cerebral vascular accidents, and brainstem tumors. The acute onset of RBD may associate with the use of antidepressants and acute withdrawal from alcohol. The diagnosis of RBD should be confirmed by polysomnography utilizing multiple-limb electromyography and synchronized digital video monitoring and demonstrate elevation of muscle tone during REM sleep along with dream enactment behavior. The differential diagnosis includes sleepwalking, nocturnal seizures, sleep apnea, and periodic limb movement disorder. Management focuses on maximizing safety, use of clonazepam/melatonin, and discussion of prognosis with patients.
Keywords: sleep; rapid eye movement sleep; REM sleep without atonia; REM sleep behavior disorder; dream enactment behavior; parasomnia; Parkinson's disorders; synucleinopathy; neurodegenerative disease